Silver Ion High-Performance Liquid Chromatography—Atmospheric Pressure Chemical Ionization Mass Spectrometry: A Tool for Analyzing Cuticular Hydrocarbons - Vladimír Vrkoslav; Petra Horká; Jindřich Jindřich; Miloš Buděšínský; Josef Cvačka (Molecules, 2023)
Aliphatic hydrocarbons (HCs) are usually analyzed by gas chromatography (GC) or matrix-assisted laser desorption/ionization (MALDI) mass spectrometry. However, analyzing long-chain HCs by GC is difficult because of their low volatility and the risk of decomposition at high temperatures. MALDI cannot distinguish between isomeric HCs. An alternative approach based on silver ion high-performance liquid chromatography (Ag-HPLC) is shown here. The separation of HC standards and cuticular HCs was accomplished using two ChromSpher Lipids columns connected in series. A gradient elution of the analytes was optimized using mobile phases prepared from hexane (or isooctane) and acetonitrile, 2-propanol, or toluene. HCs were detected by atmospheric pressure chemical ionization mass spectrometry (APCI-MS). Good separation of the analytes according to the number of double bonds, cis/trans geometry, and position of double bonds was achieved. The retention times increased with the number of double bonds, and trans isomers eluted ahead of cis isomers. The mobile phase significantly affected the mass spectra of HCs. Depending on the mobile phase composition, deprotonated molecules, molecular ions, protonated molecules, and various solvent-related adducts of HCs were observed. The optimized Ag-HPLC/APCI-MS was applied for characterizing cuticular HCs from a flesh fly, Neobellieria bullata, and cockroach, Periplaneta americana. The method made it possible to detect a significantly higher number of HCs than previously reported for GC or MALDI-MS. Unsaturated HCs were frequently detected as isomers differing by double-bond position(s). Minor HCs with trans double bonds were found beside the prevailing cis isomers. Ag-HPLC/APCI-MS has great potential to become a new tool in chemical ecology for studying cuticular HCs.